PENGARUH JENIS KOPI DAN METODE PENYEDUKAN TERHADAP KARAKTERISTIK PH DAN WARNA SERTA ORGANOLEPTIK KOPI - Talitha, Zada Agna; Marvie, Ilham; Ahmad Zainul Fatih (Jurnal Sains dan Teknologi Pangan, 2025)
The need for optimizing coffee brewing based on bean type characteristics and consumer preferences drives research on the influence of coffee type and brewing methods on physicochemical and sensory quality. Robusta and liberica, as varieties with unique profiles, were tested using the V60, americano, and tubruk brewing methods to compare the brewing characteristics. This study aims to evaluate color and pH parameters as well as organoleptic profiles (color, aroma, taste, body, Aftertaste, and overall) with post-harvest natural and medium roasting level limitations. The research design used a two-way ANOVA and DMRT post-hoc test. The results showed that the type of coffee bean and brewing method affect the physicochemical characteristics of the coffee brew. The results of the coffee brew pH test were significantly different (<0.05) among each sample, and the color test results were significantly different (<0.05) for parameters L, a*, and b*, with no significant difference in parameters a* and b* using the V60 brewing method. The hedonic organoleptic test results showed a significant effect (<0.05) from the differences in coffee brewing methods on the attributes of color, aroma, and body. Meanwhile, the attributes of acidity, Aftertaste, and overall did not show a significant effect (>0.05).